Job satisfaction among Malaysian youth working in the oil palm plantation sector: Analysis of attraction and repulsion factors - Kamaruddin, Roslina; Amizi, Mohd; Abdullah, Norehan; Ali, Jamal; Ahmad, Siti Aznor (2016)
Oil palm is labour intensive crops where the labour issue is one of the most intransigent problems facing the industry.The negative perception towards this sector associated with the unattractive working environment which is commonly refer to dark, dirty and dangerous have distress local youth to stay away from this occupation. Thus the objective of this paper is to explore the level of job satisfaction among oil palm plantation workers in Malaysia and analysing the factors contribute to their satisfaction level. The survey was conducted in 2013 through interviews from the selected samples of oil palm plantation workers that aged ranging from 16 to 40 years old which was considered as youth category and staying within the location 5 kilometres radius within the plantation area.The Structural Equation Modelling is used to analyse the factors effecting job satisfaction among workers in the plantation sector.The study found that the government and employer policies associated with plantation worker and economic profitability offered in this sector were the most significant factors that positively contribute to the joy of working among them.While the negative relationship between working environment and perception of social job status with job satisfaction proven that these two factors were repulsion factors. Thus strengthening in policies and economic incentive, as well as re-branding the working environment and social job status seen are the best way to raise the level of job satisfaction among the plantation workers in Malaysia.